Economic Crisis, Poor Governance and the Rise of Populism: The Case of Greece - Daphne Halikiopoulou (Intereconomics, 2020)
Whereas across Western Europe, the salience of an emerging cultural cleavage has triggered the rise of right-wing populist parties that focus on immigration, in Greece the salience of the materialist cleavage exacerbated by the country's severe and protracted economic crisis gave rise to populist forces of both the right and the left.
Keywords: 330